Enhanced dye sensitized solar cell performance with high surface area thin ZnO film and PEDOT:PSS. (August 2015) - Susmitha, K.; Naresh Kumar, M.; Rajkumar, G.; Giribabu, L.; Raghavender, M.
Highlights: ZnO thin film were grown on TiO2 film using spin coat method. Photo current–density was higher in ZnO coated TiO2 based test cells. Higher IPCE was observed in higher I2 content electrolyte. ZnO layer was coated on TiO2 film for considering to the enhancement in efficiency. PEDOT:PSS used for counter electrode preparation towards reduce the cost of DSSC. Abstract: ZnO coated meso-porous nanocrystalline TiO2 films were prepared and the corresponding photoelectrodes were used in the fabrication of Dye-Sensitized Solar Cells (DSSCs) to investigate its influence along with platinum (Pt), poly(3, 4-ethylenedioxythiophene: poly (4-styrene sulfonate)) [PEDOT:PSS] counter electrodes on incident-photon-to-current conversion efficiency (IPCE) and power conversion performance ( η ). DSSCs fabricated based on the ZnO coated photoeletrodes exhibit an IPCE of 71% with η- value of 7.51 ± 0.06% [short-circuit current density ( J SC ) = 17.93 ± 0.07 mA/cm 2, open-circuit voltage ( V OC ) = 0.66 ± 0.01 V, fill factor (FF) = 0.62 ± 0.01] under Air Mass 1.5 sunlight, higher as compared to the reference DSSCs fabricated under similar conditions for ZnO free photoelectrodes, which exhibited η -value of 6.11 ± 0.02% ( J SC = 15.04 ± 0.04 mA/cm 2, V OC = 0.68 ± 0.01 V, FF = 0.60 ± 0.01) with platinum decorated counter electrodes. The higher power conversion efficiency of DSSCs fabricated based on TiO2 /ZnO electrode could be probably more competitive electron collection process due to sharper ZnO nanosoar paths.